As correspondências entre José Enrique Rodó e Miguel de Unamuno: o reencontro intelectual da Pátria Mãe com a Pátria Filha - Santos, Elisângela Da Silva (Departamento de Sociologia da Universidade de Brasília, 2016)
This article aims at analyzing some current topics in letters exchanged between the authors José Enrique Rodó (1871-1917) and Miguel de Unamuno (1864-1936). In these letters, we can see an intellectual project, that proposed to outline an exchange of ideas and relations between Spain and Latin America. Among the topics discussed, we can see: the debates of their books, the construction of a collective spirit in order to get an approach between the former Motherland and the former daughterland; their essayistic productions; political and historical conditions that Spain and Uruguay were going through; positivism and idealism, and finally, religion and science. All these elements have been discussed by the authors and will be resumed in the text in order to highlight, from his writings, an intellectual and spiritual alliance between the countries involved in the colonization process.

O presente artigo tem como objetivo analisar alguns temas presentes nas correspondências trocadas entre os autores José Enrique Rodó (1871-1917) e Miguel de Unamuno (1864-1936). Nessas cartas, podemos perceber um projeto intelectual que tinha como proposta traçar um intercâmbio de ideias e de relações entre a Espanha e a América Latina. Dentre os temas discutidos estão: os debates em torno de seus livros; a construção de um espírito coletivo com vistas a uma aproximação entre a Antiga Pátria Mãe e a Antiga Pátria Filha; suas produções ensaísticas; as condições políticas e históricas vivenciadas por Espanha e Uruguai; o positivismo e o idealismo; por fim, a religião e a ciência. Todos esses elementos foram debatidos pelos autores e serão retomados no texto com a finalidade de perceber em seus escritos uma aliança intelectual e espiritual entre os países envolvidos neste processo de colonização.
Keywords: Correspondences; Intellectuality; Hispanic-America; José Enrique Rodó; Miguel de Unamuno; correspondência; intelectualidade; América hispânica; José Enrique Rodó; Miguel de Unamuno